2016
DOI: 10.5005/jp-journals-10005-1326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Comprehensive Dental Rehabilitation on Growth Parameters in Pediatric Patients with Severe Early Childhood Caries

Abstract: Background: Children who have severe early childhood caries (S-ECC) weigh significantly less than caries-free children. The association between S-ECC and weight suggests that its timely treatment at early stages may preserve general health, in addition to preventing pain and infection.Objective: This study was conducted to evaluate whether children with untreated S-ECC had lower weight and height as compared with children with low caries and to evaluate whether full mouth rehabilitation of children with S-ECC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
2
9
0
Order By: Relevance
“…ECC impacts on quality of life, increases the risk of caries in the permanent dentition, and promotes inequalities in oral health [ 5 , 6 ]. Moreover, the consequences of untreated severe ECC (S-ECC) in young children are more serious than those of caries that develop in adulthood [ 7 ]. However, in most cases, ECC can be prevented, controlled, or even resolved if treated appropriately, even in the presence of S-ECC [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECC impacts on quality of life, increases the risk of caries in the permanent dentition, and promotes inequalities in oral health [ 5 , 6 ]. Moreover, the consequences of untreated severe ECC (S-ECC) in young children are more serious than those of caries that develop in adulthood [ 7 ]. However, in most cases, ECC can be prevented, controlled, or even resolved if treated appropriately, even in the presence of S-ECC [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This case highlights a multifactorial etiology for dental caries: diet associate with prolonged breastfeed, inadequate oral hygiene habits, low mother's education, low socioeconomic status of the family, and high sugar ingestion between meals [1,11]. In addition, it highlights the importance of an integral and articulated vision between related areas in dentistry allowing for the reestablishment and maintenance of favorable oral and general health conditions for proper development of the patient [9,13,14]. Consequences of untreated ECC include a higher risk of new carious lesions in both the primary and permanent dentitions, hospitalizations and emergency room visits, increased treatment costs, risk for delayed physical growth and development, loss of school days and increased days with restricted activity, diminished ability to learn and diminished oral health-related quality of life [10,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it highlights the importance of an integral and articulated vision between related areas in dentistry allowing for the reestablishment and maintenance of favorable oral and general health conditions for proper development of the patient [9,13,14]. Consequences of untreated ECC include a higher risk of new carious lesions in both the primary and permanent dentitions, hospitalizations and emergency room visits, increased treatment costs, risk for delayed physical growth and development, loss of school days and increased days with restricted activity, diminished ability to learn and diminished oral health-related quality of life [10,14,15]. In addition, it has been reported that appropriate dental treatment may also have a positive impact on psychological and social aspects related to the child's life [7,8,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 S-ECC, the severe form of ECC, may have a greater impact than caries during adulthood if left untreated. 7 However, several cases have indicated that ECC, even S-ECC, can be prevented or regulated, given the application of appropriate measures. 8 …”
Section: Introductionmentioning
confidence: 99%